2010
DOI: 10.1111/j.1872-034x.2010.00641.x
|View full text |Cite
|
Sign up to set email alerts
|

Relapse of hepatitis C in a pegylated‐interferon‐α‐2b plus ribavirin‐treated sustained virological responder

Abstract: A 41-year-old woman with chronic hepatitis C was treated with pegylated-interferon (PEG-IFN)-alpha-2b plus ribavirin for 24 weeks. She had hepatitis C virus (HCV) genotype 2a (1600 KIU/mL), and her liver histology showed mild inflammation and fibrosis. Four weeks after the start of the therapy, she achieved a rapid virological response (RVR) and then a sustained virological response (SVR). Serum alanine aminotransferase (ALT) levels remained within normal ranges and HCV RNA continued to be negative. However, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
(43 reference statements)
1
10
0
Order By: Relevance
“…These findings were made in a cohort of patients who sporadically tested positive for HCV RNA by nested RT-PCR within the first years after an SVR to IFN-based therapy (8). The results are consistent with reports showing residual virus in approximately 6% of SVRs by highly sensitive transcription-mediated amplification assays or nested RT-PCR (2, 10, 11), even though a relapse with high levels of viremia is exceedingly rare (12)(13)(14)(15).…”
Section: Discussionsupporting
confidence: 78%
“…These findings were made in a cohort of patients who sporadically tested positive for HCV RNA by nested RT-PCR within the first years after an SVR to IFN-based therapy (8). The results are consistent with reports showing residual virus in approximately 6% of SVRs by highly sensitive transcription-mediated amplification assays or nested RT-PCR (2, 10, 11), even though a relapse with high levels of viremia is exceedingly rare (12)(13)(14)(15).…”
Section: Discussionsupporting
confidence: 78%
“…Studies from Canada7, 20 suggest that 75%‐86% of presumed recovered subjects have HCV RNA in their PBMCs, even in the absence of HCV RNA in plasma. Furthermore, some case reports of HCV reemergence and relapse after sustained virological response (SVR) demonstrated identical sequences during viral reappearance, suggesting that the original infection had persisted at undetectable serum levels, rather than HCV reinfection 10, 12. These reports support the existence of viral reservoirs from which HCV could reemerge and suggest that PBMCs may be an important viral reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…This is a critical issue, because if residual HCV exists, there is the potential for reactivation in the setting of organ transplantation, chemotherapy, or other acquired immunosuppressive states, as reported in occult HBV infection 9. Although HCV reactivation is limited to a few case reports,10‐12 the potential for residual HCV in persons whose serum tests HCV RNA negative raises concern regarding the use of organs from presumed HCV‐recovered subjects in the transplant setting, and raises the potential that such individuals would remain at risk for the subsequent development of HCC. It is thus essential to determine whether residual HCV infection exists in persons whose serum markers suggest full recovery.…”
mentioning
confidence: 99%
“…Furthermore, a recent report showed that residual HCV RNA, which appears sporadically in treatment‐recovered patients, can be infectious in chimpanzees . However, although HCV reactivation after SVR has been described in case reports, this is a truly unusual event.…”
Section: Introductionmentioning
confidence: 98%